Rethinking Digital Intellectual Property Protection in Indonesia: Comparative Insights from Singapore and the European Union - Rufinus Hotmaulana Hutauruk; Rosalinda Rosalinda; Hari Sutra Disemadi; Lu Sudirman (Greenation Research & Yayasan Global Resarch National, 2026)
Indonesia’s current framework for removing Copyright- and trademark-infringing digital content remains fragmented, with no standardized notice-and-takedown procedure, unclear institutional oversight, and sanctions that lack deterrent effect. This study asks how Indonesia can strengthen its content-removal regime and align it with international best practices. The objective is to formulate legally sound and operational reforms by comparing Indonesia’s laws with Singapore’s regime and the European Union’s Digital Services Act (DSA) 2022. Using a normative juridical method with a comparative legal approach, the research examines statutory provisions, institutional arrangements, and enforcement mechanisms across the three jurisdictions. The findings show that the EU offers the most comprehensive and adaptive model, combining structured notice-and-action, automated measures, robust transparency duties, and independent oversight with turnover-based penalties. Singapore provides a pragmatic, moderately structured system with clear takedown pathways and a dedicated regulator (IMDA), though without automated removal obligations. Indonesia lags in procedural clarity, specialization, and proportionate sanctions. The article proposes three integrated reforms for Indonesia: (1) a standardized notice-and-takedown mechanism; (2) the establishment of an independent digital intellectual property supervisory authority; (3) strict statutory response time standards; and (4) clear, tiered platform liability rules, all of which are reinforced by proportionate, turnover-based sanctions. Grounded in progressive legal theory and Radbruch’s tripartite purpose of law, the study's significance lies in formulating a concrete, adaptive legislative roadmap capable of safeguarding intellectual property rights, compelling platform accountability, and aligning Indonesia's digital governance with international best practices.